ANALISIS KEPUASAN PENGGUNA MENGGUNAKAN METODE PIECES PADA WHATSAPP SEBAGAI APLIKASI KNOWLEDGE SHARING - Choriah Choriah; Evy Nurmiati (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Knowledge sharing has an important role in the student learning process in sharing knowledge with peers and lecturers. Now there is a text message/messenger based feature / application that helps students share knowledge such as whatsapp. But whether WhatsApp can run optimally in the knowledge sharing process or not, we don't know yet, for that it is necessary to analyze whatsapp performance. The purpose of this study is to determine the level of user satisfaction with whatsapp as an application for knowledge sharing. The method used to measure the level of user satisfaction uses the PIECES method. The results of this study indicate that WhatsApp gets an average value of 4.25 which shows that users are very satisfied in using the WhatsApp application as a knowledge sharing application.